Proteolytic signatures define unique thrombin-derived peptides present in human wound fluid in vivo. Issue 1 (December 2017) - Saravanan, Rathi; Adav, Sunil; Choong, Yeu; van der Plas, Mariena J. A.; Petrlova, Jitka; Kjellström, Sven; Sze, Siu; Schmidtchen, Artur
Abstract The disease burden of failing skin repair and non-healing ulcers is extensive. There is an unmet need for new diagnostic approaches to better predict healing activity and wound infection. Uncontrolled and excessive protease activity, of endogenous or bacterial origin, has been described as a major contributor to wound healing impairments. Proteolytic peptide patterns could therefore correlate and "report" healing activity and infection. This work describes a proof of principle delineating a strategy by which peptides from a selected protein, human thrombin, are detected and attributed to proteolytic actions. With a particular focus on thrombin-derived C-terminal peptides (TCP), we show that distinct peptide patterns are generatedin vitro by the human S1 peptidases human neutrophil elastase and cathepsin G, and the bacterial M4 peptidasesPseudomonas aeruginosa elastase andStaphylococcus aureus aureolysin, respectively. Corresponding peptide sequences were identified in wound fluids from acute and non-healing ulcers, and notably, one peptide, FYT21 (FYTHVFRLKKWIQKVIDQFGE), was only present in wound fluid from non-healing ulcers colonized byP .aeruginosa andS .aureus . Our result is a proof of principle pointing at the possibility of defining peptide biomarkers reporting distinct proteolytic activities, of potential implication for improved diagnosis of wound healing and infection.